A brief intervention for drug use, sexual risk behaviours and violence prevention with vulnerable women in South Africa: A randomised trial of the Women's Health CoOp - Wechsberg, W.M.; Jewkes, R.; Novak, S.P.; Kline, T.; Myers-Franchi, Bronwyn; Browne, F.A.; Carney, T.; Lopez, A.A.M.; Parry, C. (BMJ PUBLISHING GROUP, 2013)
Objective: To assess the impact of the Women's Health CoOp (WHC) on drug abstinence among vulnerable women having HIV counselling and testing (HCT).